Exploring the Dynamics of Insecure Attachment Styles and Cultural Sexual Scripts In Relation to Sexual Communication - Bridge, Monica (Université Saint-Paul / Saint Paul University, 2020)
The sexual relationship represents a vital ingredient of committed adult romantic relationships. Research has demonstrated that attachment styles and sexual scripts have important implications for sexual communication and sexual satisfaction. The present thesis sought to examine the influence of insecure attachment styles and cultural sexual scripts on sexual communication and satisfaction with the sexual relationship and explore the relationship between each variable. A second objective of the study was to analyze the moderating effects of gender on these relationships. A total of 94 participants were recruited and completed a questionnaire that assessed levels of attachment anxiety and avoidance, adherence to the traditional cultural sexual script, sexual communication satisfaction, and sexual satisfaction. The findings suggest that individuals high in attachment avoidance conformed to the traditional cultural sexual script, exhibited impeded sexual communication and lower levels of sexual satisfaction. Greater adherence to cultural sexual scripts was found to predict sexual satisfaction but did not have an impact on sexual communication. Furthermore, adherence to cultural sexual scripts was not found to mediate the relationship between attachment avoidance and sexual satisfaction. No moderating effects were observed for gender. The clinical implications of these findings and recommendations for further research are discussed.
Keywords: Attachment styles; Cultural sexual scripts; Sexual communication; Sexual satisfaction